Caring for the Critically Ill Obese Patient: Challenges and Opportunities. (December 2014) - Winfield, Robert D.
Obesity remains a challenging public health problem. The anatomic and physiologic complexities of obese patients make their healthcare challenging under routine circumstances, but in the setting of critical illness, these challenges are magnified. This review explores some of the unique difficulties that critical care providers face when caring for the obese patient and highlights areas in which future research is needed to provide optimal care.